2019
DOI: 10.1016/j.gca.2019.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-driven chromium isotope fractionation in ultramafic cumulate minerals: Elemental and isotopic evidence from the Stillwater Complex

Abstract: To investigate chromium diffusion kinetics in ultramafic cumulate minerals, we analyzed the Cr elemental and isotopic compositions of olivine, orthopyroxene, and chromite from the Stillwater layered intrusion. Core-to-rim compositional profiles reveal that Cr elemental concentrations decrease from 60 to 20 ppm in olivine and from 5000-4600 to 2700-2400 ppm in orthopyroxene. These zoned Cr distributions in olivine and orthopyroxene suggest that Cr was lost by diffusion into the melt. Olivine and orthopyroxene h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 78 publications
0
24
1
Order By: Relevance
“…Such hydrous fluids could easily enhance chemical diffusion between silicate phases and chromite (Shimizu and Okamoto, 2016;Bai et al, 2019). Some components in the hydrous fluids might also be partitioned into olivine around chromite and even into chromite itself, which are later expelled in the form of mineral exsolutions (e.g., Liang et al, 2018).…”
Section: Effects Of Hydrous Fluids On Chromite Surfacesmentioning
confidence: 99%
“…Such hydrous fluids could easily enhance chemical diffusion between silicate phases and chromite (Shimizu and Okamoto, 2016;Bai et al, 2019). Some components in the hydrous fluids might also be partitioned into olivine around chromite and even into chromite itself, which are later expelled in the form of mineral exsolutions (e.g., Liang et al, 2018).…”
Section: Effects Of Hydrous Fluids On Chromite Surfacesmentioning
confidence: 99%
“…The variations in Cr isotopes are reported using the notation: Most recent analyses on mantle xenoliths and mineral separates have shown that Cr isotopes are fractionated during partial melting (Xia et al 2017, Farkas et al 2013, Bai et al 2019.…”
Section: Chromium Isotopesmentioning
confidence: 99%
“…Our measurements predict that during partial melting, the silicate melts will be enriched in light isotopes, and the residues will be enriched in heavy isotopes. Recent measurements of ocean island basalts (Shen et al 2020, Bonnand et al 2020 and in mantle peridotites (Xia et al 2017, Shen et al 2018, Bai et al 2019 show that residues tend to be 0.05 ‰ heavier than products. Furthermore, the results on the time series experiments demonstrate that in non-equilibrium partial melting reactions, Cr isotope fractionations are driven by kinetic reaction and the melts are enriched in light isotopes.…”
Section: Implications For Cr Isotopes At High Temperaturementioning
confidence: 99%
“…This results in compositional variations and modifications in minerals via re-equilibration and interaction (Pagé et al 2011). Further interaction or chemical diffusion may also occur between crystallized minerals and interstitial liquids (Raedeke and McCallum 1984;Lenaz et al 2012) and between subsolidus mineral phases, such as olivine and chromite during solidification and cooling (Jackson 1961;McCallum 2002;Bai et al 2019). The extent of such interactions depends largely on the spatial migration of the melts; O' Driscoll et al (2009) proposed downward infiltration of a melt during the formation of layers in such intrusions, whereas others have argued for upward-percolation of the melts (Kaufmann et al 2018) owing to compaction of the underlying crystal pile (Irvine 1980) or a temperature gradient-driven flux (Latypov et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we conducted in situ analyses of major and trace elements and Li and O isotopes of major silicate minerals from the Ultramafic Zone of the Stillwater Complex following petrographical and mineralogical investigations. These datasets, together with the Cr isotope data from the same samples in Bai et al (2019), are used to identify elemental and isotopic variations in different rock types and to constrain potential melt/fluid activity as well as chemical interactions between various components.…”
Section: Introductionmentioning
confidence: 99%